Peningkatan Kemampuan dan Pemahaman Digital Marketing Bagi Para Pelaku BUMDes dan UMKM Desa Cidahu Kecamatan Cidahu Kabupaten Kuningan - gunawan, hadi; Lili Kamela Fitriani; Micki Watulandi (PUBLICA: Jurnal Pengabdian Kepada Masyarakat, 2023)
In today's increasingly advanced digital era, marketing products or services can not only be done in conventional ways. The development of technology and the internet has allowed business people to market their products or services online using digital marketing strategies. For BUMDes (Village-Owned Enterprises) and MSMEs (Micro, Small and Medium Enterprises), improving their ability and understanding of digital marketing can be an important factor in improving their business. With a good understanding and digital marketing skills, BUMDes and MSMEs can expand market reach, increase online visibility, and obtain greater profits. However, not all BUMDes and MSMEs have sufficient knowledge and skills in terms of digital marketing. Increased Revenue: In many cases, this training results in increased income for BUMDes and MSMEs, as it can reach more customers and increase their sales. Sustainability: Increased understanding of digital marketing also allows BUMDes and MSMEs to be more resilient to changes in the business environment, including those related to technology. Collaboration and Networking: This activity also creates opportunities for collaboration and network formation between BUMDes and MSME actors. They can learn from each other and share useful experiences. The main conclusion is that community service in improving digital marketing capabilities and understanding for BUMDes and MSMEs is a very important step in supporting the growth and sustainability of the local business sector. Through this effort, BUMDes and MSME actors